Spatial-Temporal Variability of the δ18O Values and the Snow Cover Structure on the Territory of the Meteorological Observatory of the Lomonosov Moscow State University - S. A. Sokratov; A. Yu. Komarov; Yu. K. Vasil’chuk; N. A. Budantseva; J. Yu. Vasil’chuk; Yu. G. Seliverstov; P. B. Grebennikov; D. M. Frolov (Лëд и снег)
The isotopic composition (δ18O values) of snow layers, constructing snow cover to the time of reaching maximum snow water equivalent (SWE), was compared with the isotopic content of snow precipitated over the whole the winter season 2018/19 on the territory of the Meteorological Observatory of the Lomonosov Moscow State University (Moscow, Russia). Snow-sampling was carried out in a trench 20 m long simultaneously with detailed measurements of spatial variability of the structural characteristics of snow depth. Sampling was conducted for each precipitation event over the winter season, with the amount of precipitation also documented. It was found that the spatially-distributed enrichment with heavy oxygen isotopes along the trench fell within the range of 0–3.5‰, with average values for the four main formed snow layers changing from 1.3 to 2.5‰. The enrichment was not much dependent on the age of snow layer in the snowpack, and it was even more pronounced in the upper layers. This suggests that the post-precipitated change in the isotopic composition of snow cover for the conditions of the investigated site mainly took place when the snow was exposed to the atmosphere (due to sublimation and evaporation), while the processes of dry and wet metamorphism were either less important or even led to leveling the effects of isotopic fractionation. A positive correlation was found between the isotope composition of snow and the spatially varying snow density in each layer. This is most probably related to involvement of wind influence into the snow accumulation resulting in more dense snow. The spatial variability of the isotope composition of snow in each layer was smaller than changes in snow density and snow water equivalent.